2016
DOI: 10.1007/s10803-016-2731-7
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Autism Spectrum Disorders: Current Conceptualization, and Transition to DSM-5

Abstract: Mirroring the evolution of the conceptualization of autism has been changes in the diagnostic process, including the most recent revisions to the DSM-5 and the addition of severity-based diagnostic modifiers assigned on the basis of intensity of needed supports. A review of recent literature indicates that in research stratifying individuals on the basis of autism severity, core ASD symptomology is the primary consideration. This conceptualization is disparate from the conceptualization put forth in DSM-5 in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 102 publications
0
24
0
2
Order By: Relevance
“…An individual must manifest impairments in both social communication and restricted and repetitive behavior to be diagnosed with ASD. Given this change in the DSM‐V, researchers have begun to explore whether the factor structure of existing measures aligns with the revised diagnostic criteria for ASD [e.g., Mehling & Tassé, for a review]. In a factor analytic study of the SRS based on data from both children and adults, Frazier Ratliff, et al [] and Frazier, Youngstrom, et al [] found that a two factor model (i.e., social communication and interaction, “SRS‐SCI,” and restricted, repetitive patterns of behavior, “SRS‐RRB”), consistent with the new diagnostic criteria, provided a good fit to the data and better incremental validity than the conventional use of SRS total score.…”
Section: Introductionmentioning
confidence: 99%
“…An individual must manifest impairments in both social communication and restricted and repetitive behavior to be diagnosed with ASD. Given this change in the DSM‐V, researchers have begun to explore whether the factor structure of existing measures aligns with the revised diagnostic criteria for ASD [e.g., Mehling & Tassé, for a review]. In a factor analytic study of the SRS based on data from both children and adults, Frazier Ratliff, et al [] and Frazier, Youngstrom, et al [] found that a two factor model (i.e., social communication and interaction, “SRS‐SCI,” and restricted, repetitive patterns of behavior, “SRS‐RRB”), consistent with the new diagnostic criteria, provided a good fit to the data and better incremental validity than the conventional use of SRS total score.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth remembering that social impairment goes beyond anxiety and is a characteristic symptom of several neuropsychiatric conditions such as autism spectrum disorders, schizophrenia, and stress-adjustment disorders [24][25][26][27][28]. Such disorders present either a possible etiology associated with stress or present aggravated symptoms in situations of exposure to adverse situations [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the National Insurance Disability Scheme in Australia, enacted since the completion of the DSM-5, interprets the lowest support level ("Requiring support") as usually disqualifying autistic people from eligibility for services (https:// www.ndis.gov.au/). Fortunately, academic studies suggest the "need for support" framing has shifted some attention toward disability (low adaptive functioning) as well as non-specific disability characteristics sometimes associated with autism such as low cognitive ability [31,32], without a consistent relationship between these developmental domains and core autism "symptoms" [33]. This is a good thing, as we have always believed that the focus of service provision should be on improving adaptive functioning and other personcentered goals, rather than trying to "correct" or "cure" autistic traits.…”
Section: Outcomes and Implicationsmentioning
confidence: 99%